2002
DOI: 10.1111/1467-9507.00202
|View full text |Cite
|
Sign up to set email alerts
|

The Uniqueness of the Child–Father Attachment Relationship: Fathers’ Sensitive and Challenging Play as a Pivotal Variable in a 16‐year Longitudinal Study

Abstract: This longitudinal study of forty-four families explored fathers' as compared to mothers' specific contribution to their children's attachment representation at ages 6, 10, and 16 years. In toddlerhood, fathers' and mothers' play sensitivity was evaluated with a new assessment, the sensitive and challenging interactive play scale (SCIP). Fathers' SCIP scores were predicted by fathers' caregiving quality during the first year, were highly consistent across 4 years, and were closely linked to the fathers' own int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

40
464
3
30

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 666 publications
(537 citation statements)
references
References 55 publications
(66 reference statements)
40
464
3
30
Order By: Relevance
“…First, fathers' interactive play during toddlerhood has been longitudinally associated with attachment security in later childhood and adolescence. 17 Second, fathers' speech and language interactions with infants have been positively associated with language development, and paternal depression has been shown to adversely impact this process. [18][19][20] Third, discipline practices, such as corporal punishment, have been longitudinally associated with increased child aggressive behavior.…”
mentioning
confidence: 99%
“…First, fathers' interactive play during toddlerhood has been longitudinally associated with attachment security in later childhood and adolescence. 17 Second, fathers' speech and language interactions with infants have been positively associated with language development, and paternal depression has been shown to adversely impact this process. [18][19][20] Third, discipline practices, such as corporal punishment, have been longitudinally associated with increased child aggressive behavior.…”
mentioning
confidence: 99%
“…Research has consistently demonstrated the benefits of father involvement, particularly during the child's early development e.g., language acquisition, motor skills, and social skills thus leading to positive outcomes for the child in their teenage and adult years (Flouri, 2005;Grossman et al, 2002). A number of studies have established that children who do not live with their biological father are at a greater risk of depression, low self-esteem, substance abuse, and poor performance in school when compared to their counterparts who live with both their mother and father (Antecol & Bedard, 2007;Cowan, Cowan, Pruett, Pruett, & Wong, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Se no início da formulação da teoria da vinculação por Bowlby (1972Bowlby ( , 1982, a psicologia cognitiva era um campo de estudo relativamente recente, actualmente esta área do conhecimento tem tido enormes progressos permitindo a transição da investigação baseada apenas na avaliação dos comportamentos observados em contexto naturalista (AQS) ou em situação laboratorial (Situação Estranha), para o nível da representação (H. Waters, Rodrigues & Ridgeway, 1998). Um elemento central e actual no estudo da vinculação é o de que a representação cognitiva que os pais têm da relação de vinculação é um factor que medeia a qualidade da prestação dos cuidados/de interacção que estabelecem com os seus filhos, o que se reflecte na qualidade de vinculação das crianças (Bretherton, 1985;Main, Kaplan & Cassidy, 1985;Posada, Waters, Crowell, & Lay, 1995;Grossmann et al, 2002;Tini, Corcoran, Rodrigues-Doolabh, & Waters, 2003). A teoria prevê que as actuais conceptualizações que os indivíduos têm da vinculação reflictam a organização do seu modelo interno de vinculação.…”
unclassified